1998
DOI: 10.1074/jbc.273.7.3980
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear RPL4 Gene Encodes a Chloroplast Protein That Co-purifies with the T7-like Transcription Complex as Well as Plastid Ribosomes

Abstract: We have cloned and sequenced the cDNA and the gene coding for plastid ribosomal protein L4 (RPL4) from two higher plant species, spinach and Arabidopsis thaliana. Ribosomal protein L4 is one of the ribosomal proteins for which extraribosomal functions in transcriptional regulation has been demonstrated in prokaryotes. Sequence comparison of the two plant cDNAs and genes shows that the RPL4 gene has acquired a remarkable 3 extension during evolutionary transfer to the nuclear genome. This extension harbors an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In the Populus dormant terminal buds, a total of six phosphorylation sites were identified on eight ribosomal P-proteins during the maintenance of dormancy (Liu et al, 2010). Trifa et al (1998) have showed that the L4 protein in Arabidopsis and spinach was implicated in the regulation of plastid rDNA expression and transcription. Many ribosomal proteins have a second function apart from the ribosome (Wool, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the Populus dormant terminal buds, a total of six phosphorylation sites were identified on eight ribosomal P-proteins during the maintenance of dormancy (Liu et al, 2010). Trifa et al (1998) have showed that the L4 protein in Arabidopsis and spinach was implicated in the regulation of plastid rDNA expression and transcription. Many ribosomal proteins have a second function apart from the ribosome (Wool, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While CDF2-A might repress transcription initiation by PEP at the rrn16 P1 promoter (termed P2 in spinach), CDF2-B possibly binds NEP and initiates specific transcription from the rrn16 Pc promoter. In addition, a role of RPL4 (plastid ribosomal protein L4, encoded by the nuclear Rpl4 gene) has been discussed to be involved in NEP transcription, since it co-purifies with the T7-like transcription complex in spinach (Trifa et al, 1998). The bacterial L4 has extra-ribosomal functions in transcriptional regulation (Zengel et al, 1980).…”
Section: Nep Transcription Factorsmentioning
confidence: 99%
“…The identity of these proteins, however, remained elusive so far. In addition to these factors, a number of nucleoid-binding proteins such as MFP1, DND41, PEND, DPC68, SiR, RPL4 and ET1 (Sato et al, 1993;Nakano et al, 1997;Trifa et al, 1998;Sato et al, 2001;Chi-Ham et al, 2002;Jeong et al, 2003; da Costa e Silva et al, 2004) were identified. Most of them seem to be involved in the structural integrity and membrane association of nucleoids.…”
Section: Introductionmentioning
confidence: 96%